Implementasi Framework Laravel Dalam Pengembangan Aplikasi E-Commerce Untuk Toko Jago Software - Abel Ratino; Renita Astri; Putri Anggraini (CV. ITTC INDONESIA, 2023)
This research implements the Laravel framework in the development of an e-commerce application for Jago Software Store. The component-based software development method is employed for requirements analysis, design, implementation, and testing. Laravel framework provides robust features in route management, user management, database management, and security. Components such as product management, category management, shopping cart, payment system, and delivery system are implemented with modularization, facilitating maintenance and further development. The result is an efficient and reliable e-commerce application for Jago Software Store.